The Impact of Social Media Campaigns, Digital Literacy, and Political Efficacy on Generation Z's Political Participation in the Local Elections - Muhammad Afdhal Arrazak; Muhammad Fachri Adnan (Faculty of Social Science, Universitas Negeri Padang, 2026)
Generation Z (Gen Z) constitutes a significant segment of the electorate in Indonesian general elections; however, their political participation in regional head elections remains consistently low. This limited engagement is likely influenced by factors such as exposure to inaccurate information, low political self-efficacy, and insufficient depth of digital literacy. The study aims to examine the influence of social media campaigning, digital literacy, and political efficacy on the political participation of Gen Z voters in the 2024 Pilkada in the City of Padang. A quantitative approach with a survey design was employed, involving 100 purposively selected Gen Z respondents residing in Padang. Data were analyzed using multiple linear regression to test the research hypotheses. Inferential analysis demonstrated that social media campaigning (β = 0.320, p < 0.001), digital literacy (β = 0.280, p < 0.01), and political efficacy (β = 0.410, p < 0.001) partially and simultaneously exerted positive and statistically significant effects on Gen Z’s political participation, collectively explaining 68.5% of the variance in participation. Political efficacy emerged as the strongest predictor, followed by digital literacy, which also significantly contributed to increased electoral engagement among young voters. These findings enrich the scholarly understanding of youth political participation dynamics in the digital era and offer practical implications for the General Elections Commission of Indonesia. Specifically, they underscore the need for more effective digital interventions, such as integrated social media campaigns combined with targeted digital literacy education to enhance Gen Z's active participation in future regional elections and thereby strengthen local democratic processes.